Leveraging the BERT Model for Enhanced Sentiment Analysis in Multicontextual Social Media Content - Saragih, Hondor; Manurung, Jonson (Jurnal Teknik Informatika C.I.T Medicom, 2024)
The increasing prevalence of social media platforms has led to a surge in user-generated content, necessitating advanced techniques for accurate sentiment analysis. This study investigates the application of the BERT model for sentiment analysis on multicontextual social media content, aiming to enhance sentiment classification accuracy by leveraging contextual embeddings. The research objectives include examining the effectiveness of BERT in capturing sentiments across diverse social media posts and evaluating its performance in comparison to traditional methods. The methodology involves tokenizing text content, converting tokens into contextual embeddings using BERT, and integrating multimedia features for a comprehensive sentiment analysis framework. The results from a numerical example demonstrate that the BERT model achieves a high probability of correctly classifying sentiments, with a notable improvement in accuracy and a low cross-entropy loss. These findings underscore the model's capability to understand contextual nuances and its potential to optimize social media monitoring and analysis processes. The study also highlights limitations such as the need for larger and more diverse datasets and the inclusion of multimedia content to enhance generalizability. Future research should explore hybrid models and address ethical considerations to ensure data privacy and mitigate biases. This work contributes to advancing theoretical frameworks and offers practical implications for businesses and marketers seeking to leverage sentiment analysis for informed decision-making and improved customer engagement strategies.